2019
DOI: 10.1016/j.jot.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Haem oxygenase-1 induction prevents glucocorticoid-induced osteoblast apoptosis through activation of extracellular signal–regulated kinase1/2 signalling pathway

Abstract: BackgroundHigh-dose glucocorticoid (GC) therapy always causes osteoporosis partly by inducing osteoblast apoptosis. However, the underlying mechanisms of GC-induced apoptosis remain elusive. Haem oxygenase-1 (HO-1) is a cytoprotective protein that rescues cells from H2O2 or high glucose–induced apoptosis. In bone metabolism, HO-1 also participates in osteoclast and osteoblast differentiation.ObjectiveThe present study aimed to investigate the protective role of HO-1 against GC-induced osteoblast apoptosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The GO enrichment analysis showed that Epimedium mainly exerts its therapeutic effect on SANFH through cell proliferation and apoptosis, cytokine expression, and reactive oxygen reaction. The specific mechanism of SANFH remains unclear, but it is certain that the apoptosis process of osteoblasts and osteoclasts and the survival status of osteoclasts are affected by glucocorticoids [10][11][12] , and SANFH may also be associated with the hypoxia-inducible factor-1α pathway [13] . Thus, promoting angiogenesis, osteoblast differentiation, and inhibiting osteoclast proliferation through certain components can slow the onset of SANFH [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The GO enrichment analysis showed that Epimedium mainly exerts its therapeutic effect on SANFH through cell proliferation and apoptosis, cytokine expression, and reactive oxygen reaction. The specific mechanism of SANFH remains unclear, but it is certain that the apoptosis process of osteoblasts and osteoclasts and the survival status of osteoclasts are affected by glucocorticoids [10][11][12] , and SANFH may also be associated with the hypoxia-inducible factor-1α pathway [13] . Thus, promoting angiogenesis, osteoblast differentiation, and inhibiting osteoclast proliferation through certain components can slow the onset of SANFH [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described. (50,51) The immunoreactive bands were visualized with chemiluminescence reagent (Millipore, Billerica, MA, USA), and photographed using ChemiDoc™ Touch Imaging System (Bio-Rad). Rabbit primary antibodies, including antibodies against active β-catenin and GAPDH, and horseradish peroxidase (HRP)-conjugated antirabbit secondary antibody were all purchased from Cell Signaling Technology and used at 1:2000 dilution.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Increase in the apoptosis of osteoblasts and osteocytes, prolongation of the life span of osteoclasts and endothelial cell apoptosis, and inhibition of osteoblast and osteoclast precursor production are all directly affected by the use of glucocorticoids (Kerachian et al, 2009;Weinstein et al, 2017). Osteoblasts, as the main target of glucocorticoids, play important roles in the process of bone formation; further, dexamethasone (Dex) has been reported to induce apoptosis of mouse osteoblasts (Brennan-Speranza et al, 2012;Gamez et al, 2016;Gu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%